Characteristics of the Neuronal Firing Patterns in the Subthalamic Nucleus with Graded Dopaminergic Cell Loss in the Nigrostriatal Pathway - Park, Sunghee E.; Youn, Inchan; Suh, Jun Kyo; Song, Kang-Il (2015 37TH ANNUAL INTERNATIONAL CONFERENCE OF THE IEEE ENGINEERING IN MEDICINE AND BIOLOGY SOCIETY (EMBC), 2015)
The aim of this study was to evaluate the neuronal firing changes in the subthalamic nucleus (STN) in a graded mouse model of Parkinson's disease. Unilateral graded dopaminergic cell loss in the substantia nigra pars compacta was achieved by injecting different concentrations of 6-hydroxydopamine (6-OHDA) in the right medial forebrain bundle. Electrophysiological analysis of neuronal firing patterns in the STN revealed an increased firing rate, burst index, and interspike interval coefficient of variation in groups treated with higher 6-OHDA concentrations. The results of this study suggest the detailed pathophysiological characteristics of Parkinson's disease in a mouse model.